50 Biological Variability of Soluble ST2 in Stable Chronic Heart Failure. (31st May 2014) - Piper, Susan; Hipperson, Doma; deCourcey, Julia; Sherwood, Roy; George Amin-Youssef, Ajay Shah; McDonagh, Theresa
Abstract : Purpose: The evidence for serially monitoring patients with the B-Type Natriuretic Peptides (BNP/NT-proBNP) to detect deterioration in heart failure symptoms has shown mixed results. This may be explained by high biological variability (BV) and reference change values (RCV) of these peptides meaning that large rises or falls in concentration are necessary to produce a clinically meaningful change. ST2 is a member of the IL-33 receptor family. It is involved in the development of myocardial fibrosis and hypertrophy. Unlike the natriuretic peptides, circulating soluble ST2 (sST2) concentrations are not affected by obesity, age, atrial fibrillation, renal function or the aetiology of the cardiomyopathy. They may therefore, be better biomarkers for disease monitoring. No studies have reported on the BV or RCV of sST2 in the monitoring of patients with stable chronic heart failure (CHF). Methods: We prospectively studied patients with CHF due to LV systolic dysfunction. All patients were stable for one month prior to enrolment and on optimum evidence based heart failure medication. Mean age was 66.5 +/- 11.02 years; 77% male; 39% IHD; 42% NYHA I, 58% NYHA II. Mean EF 31.45 +/- 6.48%. Blood samples were drawn from 31 patients one hour apart on day one, with a further sample drawn one month later. Results from 4 patients who had deteriorated between time points (CV admission, increase in diuretic therapy/change in HF medication, or change in NYHA class) were excluded from the one month analysis. Results: Median BNP concentrations at baseline, one hour and one month were 230 ng/l (IQR 1040), 253 ng/l (IQR 718.8) and 187 ng/l (IQR 629) respectively. Median sST2 at baseline, one hour and one month were 16.29 ng/ml (IQR 9.29), 15.66 ng/ml (IQR 11.23) and 17.29 ng/ml (IQR 7.65) respectively. Within hour intraindividual variability was 7.5% and 5.6% for BNP and sST2 respectively (p = 0.151). Within month intraindividual variability was 22% for BNP and 8.5% for sST2 (p = 0.008). Reference change values within one hour and one month were 31% and 65% for BNP and 19% and 26% for sST2. Conclusion: sST2 shows significantly less intraindividual variability over a one month time period compared with BNP. Changes of only 26% for sST2 compared to 65% for BNP are needed to indicate an altered clinical status over the same time period. These findings suggest that sST2 may be superior to BNP for serial monitoring of patients with chronic heart failure and justify further research in this area.